Analisis Reaksi Pasar Modal Sebelum Dan Sesudahkeputusan Bank Indonesia Mengenai Suku Bunga (Studi Pada Perusahaan Lq-45 Yang Terdaftar Pada Bei Periode Agustus 2019 – Januari 2020) - PutriYulieanFajarwati; Nurasik (Research Parks Publishers, 2021)
The development of capital market activities can not be separated from the role of investors as investors and disclosure of information as consideration of investor decision making.This research aims to find out how the capital market reacts before Bank Indonesia's decision on interest rates.And to find out how the capital market reacted after Bank Indonesia's decision on interest rates.This research uses quantitative research that is event study. Data collection of financial statements at the Investment Gallery of the Indonesia Stock Exchange, University of Muhammadiyah Sidoarjo.The population in this study includes LQ45 companies that have been listed on the Indonesia Stock Exchange, with sampling techniques namely total sampling.Data analysis using T-test. The results of this study prove that there is a difference in the average abnormal return before and after Bank Indonesia's decision on interest rates as evidenced by the value of Sig.(2-tailed) is 0.000 less than 0.005 and there is a difference in average trading volume activity before and after Bank Indonesia's decision on interest rates as evidenced by the value of Sig.(2- tailed) 0.000 less than 0.005.